The Effect of Profit Management and Tax Avoidance on Company Value : (Empirical Study on the Retail Trade Sector Listed on the IDX in 2019 – 2024) - Bagas Setya Hermawan; Agus Budi Santosa (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of tax avoidance and profit management on the value of companies in the retail trading sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2024 period. This study uses a quantitative approach with multiple linear regression analysis methods. The research data is obtained from the company's officially published annual financial statements. The results show that tax avoidance has a significant effect on company value, which indicates that an effective tax management strategy is able to increase after-tax profits and strengthen investor perception. In addition, profit management has also been shown to have a significant effect on company value, which shows that profit reporting arrangements can be used as a positive signal for investors in assessing the company's performance and prospects. These findings support signal theory and agency theory, which explain that profit and tax management practices are carried out to reduce information asymmetry and increase company value. Simultaneously, the two independent variables are able to explain most of the variation in company value, although there are still other factors outside the research model that also affect the company's value.